One Hippo and many masters: differential regulation of the Hippo pathway in cancer. (11th August 2014) - Romano, David; Matallanas, David; Frederick, Dennie T.; Flaherty, Keith T.; Kolch, Walter
Abstract : The Hippo/MST2 (mammalian sterile 20-like kinase 2) pathway is a signalling cascade evolutionarily conserved in its structure. Originally described in Drosophila melanogaster as a regulator of organ size, this pathway has greater functions in mammals. Disturbance of mammalian MST2 pathway is associated with tumorigenesis by affecting apoptosis, cell cycle and polarity. In addition, this pathway has been shown to cross-talk with mitogenic pathways at multiple levels. In the present mini-review, we discuss our contribution highlighting the regulation of MST2 signalling by frequently observed oncogenic perturbations affecting mitogenic pathways. In particular, we review the role of RAS isoforms and PI3K (phosphoinositide 3-kinase)/Akt in the regulation of MST2 activity by phosphorylation. We also put the emphasis on RAF-induced control of MST2 signalling by protein–protein interactions. Finally, we recapitulate some of the direct mechanisms, such as ubiquitin-dependent degradation or gene silencing by promoter hypermethylation, involved in MST2 pathway component down-regulation in cancers.